Controle de ferrugem asiática (Phakopsora pachyrhizi Sidow) na cultura da soja - Ugalde, Mauro Giuliani (2005)
The Asian Soybean Rust (Phakopsora pachyrhizi Sidow), was recently found in Brazil. The disease has caused serious yield reduction. The lack of knowledge about many aspects of this disease, experiments were run out in order to get control strategies. The initial research goal included the lab and greenhouse work with Phakopsora pachyrhizi, under controlled conditions. In addition, it was evaluated the reaction of soybean cultivars to Phakopsora pachyrhizi, the efficacy of chemical control under preventative and curative applications of Pyraclostrobina and Epoxiconazol, and the effect of canopy coverage, gallonage (L/ha) and the utilization of adjuvants on fungicides efficacy. It was observed partial resistance of soybean cultivars. Also, an increase of susceptibility as reproductive phase get closed was evaluated. Preventative and curative effect was determined at 42 and 36 days, respectively. The number of droplets and gallonage influenced de efficiency of Pyraclostrobina + Epoxiconazol. The addition of adjuvant did not result on fungicide efficiency increase